University Transformation and Curriculum Redesign in the Area of Reason and Faith and Pastoral Care at Universidad Politécnica Salesiana on its 30th Anniversary - Reyes, Johan Méndez; Arízaga, Xavier Merchán (Journal of Ecohumanism, 2024)
To continue with the university transformation processes that have characterized Latin America in recent decades, the Ecuadorian government has promoted significant changes in its educational policy, demanding a curricular review in higher education institutions. The Universidad Politécnica Salesiana (UPS) responded to this demand with a comprehensive redesign of its curricula, aimed at providing a complete education for its students. This redesign encompassed interdisciplinary aspects, including research, outreach, teaching, collaborative methodologies, the use of new technologies, and the strengthening of Salesian charisma and identity. This paper aims to analyze this transformation and the curricular redesign of the Área Razón y Fe and Pastoral at UPS over its 30 years. Using a hermeneutic methodology, the concepts and positions that help understand its evolution are interpreted. It is concluded that UPS has met the challenge of viewing education as a dynamic system that integrates global and local, science, research, and service to vulnerable communities.